Regulation of the Thermoelectric Properties of Perovskite RECoO3 Ceramics via High-Entropy Engineering - Kezhen Zhang; Chengchao Yang; Xianpeng Ao; Yulong Zhao; Weihao Tan; Jinglong Wu; Bin Liu; Kun Dong; Liangwei Chen; Lan Yu (Crystals)
Entropy engineering has been demonstrated to be an effective strategy to regulate the thermoelectric properties of materials. In this work, we report a series of single-phase cubic (La0.25Sr0.25Ba0.25Ca0.25)CoO3 (LSBC), (La0.25Nd0.25Sr0.25Ba0.25)CoO3 (LNSB), and (La0.2Nd0.2Sr0.2Ba0.2Ca0.2)CoO3 (LNSBC) ceramics based on high-entropy design in the Re site of perovskite RECoO3. Electron microscopy results indicate that the three samples have high crystallinity and exhibit a clear pore structure with rich lattice defects. Electrical transport measurements show that LNSB and LNSBC show metallic conductive behaviors with the lowest resistivity of only 2.25 mΩ cm at 973 K, while LSBC exhibits a semiconductor–metal transition at around 650 K due to the lower average chemical valences in the RE site. Meanwhile, the low average chemical valences also cause the increasing proportion of Co4+ due to the requirement of charge neutrality of the samples, which inhibits their Seebeck coefficients. However, compared with the reported Co-based perovskite oxides, their thermal conductivities are greatly reduced owing to high-entropy enhanced lattice scattering. LSBC in particular obtains the lowest thermal conductivity of 1.25 W·m−1·K−1 at 937 K, while LNSB and LNSBC characterized by high carrier thermal conductivity exhibit a thermal conductivity of 1.52 W·m−1·K−1 at the same temperature. These findings reveal that high-entropy design in the RE site of perovskite RECoO3 ceramics enables the effective reduction of thermal conductivity and the maintenance of the excellent electrical properties simultaneously, which provides a novel route for the development of high-performance thermoelectric materials.